Structural and Functional Characterization of the Streptococcus pneumoniae RrgB Pilus Backbone D1 Domain - Gentile, Maria Antonietta (American Society for Biochemistry and Molecular Biology, 2011)
Streptococcus pneumoniae expresses on its surface adhesive pili, involved in bacterial attachment to epithelial cells and virulence. The pneumococcal pilus is composed of three proteins, RrgA, RrgB, and RrgC, each stabilized by intramolecular isopeptide bonds and covalently polymerized by means of intermolecular isopeptide bonds to form an extended fiber. RrgB is the pilus scaffold subunit and is protective in vivo in mouse models of sepsis and pneumonia, thus representing a potential vaccine candidate. The crystal structure of a major RrgB C-terminal portion featured an organization into three independently folded protein domains (D2–D4), whereas the N-terminal D1 domain (D1) remained unsolved. We have tested the four single recombinant RrgB domains in active and passive immunization studies and show that D1 is the most effective, providing a level of protection comparable with that of the full-length protein. To elucidate the structural features of D1, we solved the solution structure of the recombinant domain by NMR spectroscopy. The spectra analysis revealed that D1 has many flexible regions, does not contain any intramolecular isopeptide bond, and shares with the other domains an Ig-like fold. In addition, we demonstrated, by site-directed mutagenesis and complementation in S. pneumoniae, that the D1 domain contains the Lys residue (Lys-183) involved in the formation of the intermolecular isopeptide bonds and pilus polymerization. Finally, we present a model of the RrgB protein architecture along with the mapping of two surface-exposed linear epitopes recognized by protective antisera.